(3GdHGYK Ydi EfcGQ GdHOY hGdMhGOKs - (3TgGH GdOjf CHh eMeO YHO GdQMef Hf ESeGYjd Hf EHQGgje GdTGaYjs
(3ChdgG (B:s
(3bGd GdTjN fGUQ GdSfI TgGH GdOjf CHh eMeO GdMeO ddg gGOi GdhQi WQa GdgOi hHYO agPG cJGH LeYJg eMPQkG ef GdHOY RLQkG def hab cPdc hGQJOY eeJKdkG Hg bhd QH GdYGdejf s
(3BNQgG (B:s
(3hbO bGd GdEeGe GdTGaYi QMeg Gddg JYGdi fMhkG ef gPG Gdbhd ai QhGjI YHO Gddg Hf YeQ GdYeQi Yf fGaY Yf Hf YeQGf Cf GdfHi Udi Gddg Ydjg hSde bSe jhe NjHQ ddaGQS Sgejf hddQGLd SgekG hddg SHMGfg hJYGdi CYde hgPG BNQ cJGH GdHGYK Ydi EfcGQ GdHs
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B9s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdESdGejs